Primary Therapy of Early Breast Cancer: Evidence, Controversies, Consensus - Untch, Michael; Thomssen, Christoph; Bauerfeind, Ingo; Braun, Michael; Brucker, Sara Y.; Felberbaum, Ricardo; Hagemann, Friederike; Haidinger, Renate; Hönig, Arnd; Huober, Jens; Jackisch, Christian; Kolberg, Hans-Christian; Kolberg-Liedtke, Cornelia; Kühn, Thorsten; Lüftner, Diana; Maass, Nicolai; Reimer, Toralf; Schneeweiss, Andreas; Schumacher-Wulf, Eva; Schütz, Florian; Thill, Marc; Wuerstlein, Rachel; Fasching, Peter A.; Harbeck, Nadia (Geburtshilfe und Frauenheilkunde, 2019)
The results of the international St. Gallen Consensus Conference for the treatment of patients with primary breast cancer were discussed this year by a working group of leading breast cancer experts in view of the therapy recommendations for everyday clinical practice in Germany. Three of the breast cancer experts are also members of this yearʼs St. Gallen panel. The comparison of the St. Gallen recommendations with the annually updated treatment recommendations of the AGO 2019 as well as the S3 guideline is useful, since the recommendations of the St. Gallen panel represent the opinions of experts from various countries and disciplines. The recommendations of the S3 guideline and AGO are based on evidence-based research of the literature. This yearʼs 16th St. Gallen conference featured the motto “Magnitude of clinical benefit”. In addition to the evidence-based data, each therapeutic decision must also undergo a benefit/risk assessment of the patientʼs individual situation and be discussed with the patient.Die Ergebnisse der internationalen St.-Gallen-Konsensus-Konferenz zur Behandlung des primären Mammakarzinoms wurden auch dieses Jahr von einer Arbeitsgruppe führender Brustkrebsexperten vor dem Hintergrund der Therapieempfehlungen für den Klinikalltag in Deutschland diskutiert. Drei der Brustkrebsexperten sind zugleich Mitglieder des diesjährigen St.-Gallen-Panels. Der Vergleich der St.-Gallen-Empfehlungen mit den jährlich aktualisierten Therapieempfehlungen der Arbeitsgemeinschaft Gynäkologische Onkologie (AGO-Mamma 2019) sowie der S3-Leitlinie ist sinnvoll, da die Empfehlungen des St.-Gallen-Panels ein Meinungsbild von Experten unterschiedlicher Länder und Fachdisziplinen darstellen. Die Empfehlungen der S3-Leitlinie und AGO basieren dagegen auf einer evidenzbasierten Literaturrecherche. Die diesjährige 16. St.-Gallen-Konferenz stand unter dem Motto „Magnitude of clinical benefit“. Neben der evidenzbasierten Grundlage muss jede Therapieentscheidung auch einer Nutzen-Risiko-Abwägung für die individuelle Situation einer Patientin unterzogen und mit der Patientin besprochen werden.
Keywords: St. Gallen consensus 2019; early breast cancer; locoregional therapy; axilla; neoadjuvant treatment; systemic therapy